The contribution to research into hydrostatic bearings - Borojev, Ljubomir (Journal of Production Engineering, 1990)
The paper presents one part of the researches considering the hydrostatic bearing system for machine tools spindles. Performed investigations refer mainly to experimental model design and its testing. After a short dealing with some hydrostat hearings parameters, the problems related to the manufacture are pointed out. Further, the calculation procedure of radial hydrostatic bearings for a grinding machine spindle is discussed. The fundamental data about construction and manufacture of some parts of experimental model are given. Main characteristics of spindle drive and whole hydraulic installation are cited too. The performances investigation is described in detail, and some of obtained results are presented. The comparison of experimental and calculated results is done with analysis of their deviation. Finally, the brief consideration about performed research phase is given and the possibility of precisely determination of hydrostatic bearing performances, using such a way, is pointed out.